ELDERLY DEVELOPMENT AND ELDERLY RIGHTS AFFECTING THE ELDERLY QUALITY OF LIFE IN KHAM THALE SO DISTRICT, NAKHON RATCHASIMA PROVINCE - Anothaiphaiboon, Siamnoi (Journal of MCU Nakhondhat, 2023)
The research purposes were 1) to study the elderly quality of life; 2) to analyze the elderly development and elderly rights affecting the elderly quality of life; and 3) to propose guidelines for developing the quality of life of the elderly in Kham Thale So District, Nakhon Ratchasima Province. This was the quantitative and qualitative research. The quantitative research sample group was the 400 elderly, the research instrument was the questionnaire; the qualitative research’s key informants were the 20 elderly, the research instrument was the in - depth questionnaire. The data analysis statistics were the frequency, percentage, mean, standard deviation, multiple regression analysis, and correlation analysis. The research findings were 1) the elderly quality of life in Kham Thale So District, Nakhon Ratchasima Province found the overall was at high level; the descending mean were the good physical aspect, followed by the social relationship aspect, the environment aspect, and psychological aspects, respectively; 2) the elderly development and the rights of the elderly found that the aspect of elderly promotion and development, the aspect of social protection system for the elderly, the aspect of management for the development of work on the elderly, the aspect of medical services, the aspect of vehicles as appropriate, the aspect of assistance for the elderly who are harmed by abuse, the aspect of subsidy of subsistence allowance, and the aspect of assistance for the management of dead bodies according to tradition affected the elderly quality of life in Kham Thale So District, Nakhon Ratchasima Province at statistical significance level .05; and 3) the promotion and development of the long - term care system for the elderly, prepare all sectors to be ready to meet the long - term care needs in both urban and rural areas, work integrated in all sectors, create opportunities for the elderly to access government services, and encourage the elderly to have appropriate activities.